Association of HLA‐G 3′ untranslated region polymorphisms with antibody response against Plasmodium falciparum antigens: preliminary results. Issue 1 (10th June 2013) - Sabbagh, A.; Courtin, D.; Milet, J.; Massaro, J. D.; Castelli, E. C.; Migot‐Nabias, F.; Favier, B.; Rouas‐Freiss, N.; Moreau, P.; Garcia, A.; Donadi, E. A.
Abstract Host and Plasmodium interactions result in highly variable clinical phenotypes, partly explained by the nature and level of anti‐malarial antibody response. Human leukocyte antigen (HLA)‐G can create a tolerogenic environment, allowing parasites to escape from anti‐malarial immunity. We performed a family‐based association study encompassing 483 Sereer individuals (261 children and their parents), and reported two independent signals at the HLA‐G 3′ untranslated region associated with antibody response to specific Plasmodium falciparum blood stage antigens, previously associated with malaria protection: (i) +3010G together with +3142C with total IgG and IgG1 against GLURP and (ii) +3196G with IgG3 against MSP2. While these results require further investigation, they suggest for the first time a role of HLA‐G in the regulation of humoral immune response in malaria.